2006
DOI: 10.1261/rna.115606
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating kissing stem–loop interactions mediate 5′ scanning-dependent translation by a viral 3′-cap-independent translation element

Abstract: The 39-untranslated regions (UTRs) of a group of novel uncapped viral RNAs allow efficient translation initiation at the 59-proximal AUG. A well-characterized model is the Barley yellow dwarf virus class of cap-independent translation elements (BTE). It facilitates translation by forming kissing stem-loops between the BTE in the 39-UTR and a BTE-complementary loop in the 59-UTR. Here we investigate the mechanisms of the long-distance interaction and ribosome entry on the RNA. Upstream AUGs or 59-extensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 57 publications
(82 reference statements)
3
78
1
4
Order By: Relevance
“…2B). The translational efficiency was determined by the ability of the 3Ј BTE elements to function in the 5Ј leader of a luciferase reporter or by the ability to inhibit translation as described elsewhere (2,20). It was found that the binding of eIF4F to 3Ј BTE and mutants expressed as association constants (K a values) correlated well with the core translation abilities of the mutants with one exception, BTEBF (Fig.…”
Section: Translation Efficiencies Of 3ј Bte and Mutants Correlatementioning
confidence: 92%
See 4 more Smart Citations
“…2B). The translational efficiency was determined by the ability of the 3Ј BTE elements to function in the 5Ј leader of a luciferase reporter or by the ability to inhibit translation as described elsewhere (2,20). It was found that the binding of eIF4F to 3Ј BTE and mutants expressed as association constants (K a values) correlated well with the core translation abilities of the mutants with one exception, BTEBF (Fig.…”
Section: Translation Efficiencies Of 3ј Bte and Mutants Correlatementioning
confidence: 92%
“…BYDV affects cereal crops such as wheat, barley, oats, and grasses and is spread by several aphid species severely limiting food grain production and causing yield losses resulting in food scarcity (1). BYDV belongs to the Luteoviridae family, has a genome which is a positive sense RNA Ϸ5700 nucleotides long, and is lacking both a 5Ј cap (m 7 GpppX) and a poly(A) tail (2). In eukaryotes, the 5Ј cap is the binding site for eukaryotic initiation factors (eIFs) eIF4F and eIFiso4F (isozyme form of eIF4F present in higher plants).…”
Section: Barley Yellow Dwarf Virus (Bydv)mentioning
confidence: 99%
See 3 more Smart Citations